Nuclear Mechanics within Intact Cells Is Regulated by Cytoskeletal Network and Internal Nanostructures. Issue 18 (3rd April 2020) - Zhang, Jitao; Alisafaei, Farid; Nikolić, Miloš; Nou, Xuefei A.; Kim, Hanyoup; Shenoy, Vivek B.; Scarcelli, Giuliano
Abstract: The mechanical properties of the cellular nucleus are extensively studied as they play a critical role in important processes, such as cell migration, gene transcription, and stem cell differentiation. While the mechanical properties of the isolated nucleus have been tested, there is a lack of measurements about the mechanical behavior of the nucleus within intact cells and specifically about the interplay of internal nuclear components with the intracellular microenvironment, because current testing methods are based on contact and only allow studying the nucleus after isolation from a cell or disruption of cytoskeleton. Here, all‐optical Brillouin microscopy and 3D chemomechanical modeling are used to investigate the regulation of nuclear mechanics in physiological conditions. It is observed that the nuclear modulus can be modulated by epigenetic regulation targeting internal nuclear nanostructures such as lamin A/C and chromatin. It is also found that nuclear modulus is strongly regulated by cytoskeletal behavior through a robust mechanism conserved in different culturing conditions. Given the active role of cytoskeletal modulation in nearly all cell functions, this work will enable to reveal highly relevant mechanisms of nuclear mechanical regulations in physiological and pathological conditions. Abstract : All‐optical Brillouin microscopy and 3D chemomechanical modeling are used to investigate the regulation of nuclear mechanics. It is observed that the nuclear modulus can be modulated by epigenetic regulation targeting internal nuclear nanostructures such as lamin A/C and chromatin. It is also found nuclear modulus is strongly regulated by cytoskeletal behavior through a robust mechanism conserved in different culturing conditions.